Community Empowerment through Legal Education: Enhancing Legal Awareness in Village Communities - Donny Setha (CV. Creative Tugu Pena, 2024)
The objective of this study is to assess the efficacy of community empowerment initiatives that incorporate legal education in enhancing legal awareness within rural communities. Qualitative research methods were employed to obtain data via in-depth interviews, participatory observation, and document analysis. The findings indicated that legal education grounded in community engagement can facilitate a deeper comprehension of legal rights and obligations, fortify the community's capacity in deterring legal transgressions, and inspire active involvement in local conflict resolution. Consequently, this study proposes that legal education responsive to the needs of rural communities can serve as an effective vehicle for community empowerment. The implementation of legal education can serve as a strategic instrument for empowerment, addressing the aforementioned gap and enhancing the capacity of communities to safeguard themselves from unlawful actions and to advocate for their rights in an autonomous manner